Implementasi Inovasi Bank Jek (Pemanfaatan Jerami, Eceng Gondok, dan Keong Sebagai Pupuk Serta Ecoenzyme Untuk Pembibitan Mangrove) Pada TJSL Program Sedari Kang Hari - Ismail, Taufik; Insaniah, Cita; Andhika, M.; Fedryansyah, Muhammad (HK-Publishing, 2023)
AbstractThe Sedari Kang Hari (Green, Sustainable and Independent Village) program is implemented by PT Pertamina Patra Niaga Fuel Terminal Cikampek in Sedari Village, Cibuaya District, Karawang Regency. The program focuses on aspects of biodiversity, community empowerment and disaster response. One implementation is related to efforts to mitigate abrasion disasters by establishing conservation areas to protect biodiversity planted with mangroves. Mangrove planting is carried out using seeds that are nursed by the community. The problems that arise are the success rate of mangrove planting which is only 50% and the availability of seeds is still not sustainable. This problem was answered by implementing Bank Jek's innovation. Bank Jek's innovation is based on the problems and potential availability of raw materials in the form of waste straw, water hyacinth and snails to produce Bank Jek products, namely in the form of organic fertilizer and ecoenzymes which contain important nutrients for mangrove plants. Bank Jek's innovation provides value in the mutual cooperation involvement of various parties, including the government, community, conservation groups, and especially farmers in achieving program success. Changes in the behavior of farmers who previously burned straw waste and used chemical pesticides for snail pests have reduced their intensity, thus directly contributing to reducing greenhouse gas emissions and improving the condition of rice fields. The Bank Jek innovation produced has been marketed with the legality of product quality tests from the Sucofindo laboratory. Bank Jek's innovation with its product results is able to increase the availability of seeds in a sustainable manner and increase the success of mangrove planting to more than 70% as well as value conversion from the level of seeding and planting achievements and when compared with conditions before the implementation of the innovation with indicators of savings in purchasing / replacing seeds and maintenance as well as conversion of the use of fertilizer and ecoenzyme products results in IDR 13,000,000/year.Keywords: Bank Jek, Straw, Water Hyacinth, Snail, MangroveÂ AbstrakProgram Sedari Kang Hari (Kampung Hijau, Lestari, dan Mandiri) dilaksankan Oleh PT Pertamina Patra Niaga Fuel Terminal Cikampek di Desa Sedari, Kecamatan Cibuaya, Kabupaten Karawang. Program berfokus pada aspek keanekaragaman hayati, pemberdayaan masyarakat, dan tanggap kebencanaan. Salah satu implementasinya yaitu terkai dengan upaya mitigasi bencana abrasi dengan penetapan area konservasi perlindungan kenaekaragaman hayati yang ditanami mangrove. Penanaman mangrove dilakukan dengan menggunakan bibit yang dilakukan pembibitannya oleh masyarakat. Permasalahan yang timbul yaitu tingkat keberhasilan penanaman mangrove yang hanya 50% dan ketersedian bibit yang masih belum keberlanjutan. Permasalahan tersebut terjawab dengan diterapkannya inovasi Bank Jek. Inovasi Bank Jek didasarkan atas permasalahan serta potensi ketersedian bahan baku berupa limbah jerami, eceng gondok, dan keong untuk dihasilkan produk Bank Jek yaitu berupa pupuk organik dan ecoenzym yang mengandung unsur hara penting untuk tanaman mangrove. Inovasi Bank Jek memberikan value terhadap keterlibatan gotong royong berbagai pihak baik itu pemerintah, masyarakat, kelompok konservasi, dan khsusnya petani dalam mencapai keberhasilan program. Perubahan perilaku petani yang sebelumnya membakar limbah jerami dan menggunakan peptisida kimia untuk hama keong menjadi berkurang intensitasnya sehingga secara langsung berkontribusi terhadap penggurangan emisi gas rumah kaca dan perbaikan kondisi tanah persawahan. Inovasi Bank Jek yang diproduksi telah dipasarkan dengan legalitas uji kualitas produk hasil laboratorium Sucofindo. Inovasi Bank Jek dengan hasil produknya tersebut mampu meningkatkan ketersedian bibit secara berkelanjutan dan meningkatkan keberhasilan penanaman mangrove menjadi lebih dari 70% serta konversi nilai dari tingkat capaian pembibitan dan penanaman serta jika dibandingkan dengan kondisi sebelum penerapan inovasi dengan indikator penghematan pembelian / ganti bibit dan perawatan serta konversi penggunaan produk pupuk dan ecoenzym maka dihasilkan Rp 13.000.000/tahun.Kata Kunci: Bank Jek, Jerami, Eceng Gondok, Keong, Mangrove